Implementation of the “word” concept of in the poetry of Zinaida Gippius (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article described an example of an unusual implementation of the concept «word» in poetry of the one’s of the most original authors of Russian Symbolism – Zinaida Gippius. A specific feature of her poems is a mystical view of the world. It’s main problem is comprehension the transcendent Truth and God. Thereby a major question we can find in Z. Gippius’ works is the possibility of verbal transmission of mystical experiences. The concept «word» in Z. Gippius’ poems was implemented doubly. On the one hand, the word is a symbol of God, on the other hand, it often becomes absolutely powerless in transmission of transcendental experience. This ambivalence of the concept implementation makes Z. Gippius’ poetry dialectical.
Keywords: word; implementation; silence; transcendence; Truth; God